(untitled) (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2025)
With the exponential advancement of sophisticated artificial intelligence tools, second language educators need to embrace this inevitable educational shift by possessing a more comprehensive understanding of how to maximize the full benefits of these powerful, technology-driven learning supports in their regular teaching and learning enterprises. With respect to the above-mentioned notion, the researchers undertook this small-scale library study using a thematic analysis approach. With the support of a thematic analysis approach, the researcher can potentially yield more comprehensible, systematic, and contextualized results as the prior finding were subsumed into identical research themes. Thus, the researchers conducted an exhaustive thematic analysis of 30 previous artificial intelligence tool studies to produce more accurate research outcomes. The thematically-categorized findings unraveled that the constant utilization of artificial intelligence tools can be actualized owing to the provision of adequate professional development trainings, which may more likely result in the attainment of fruitful educational outcomes.